The Success of a Screening Program Is Largely Dependent on Close Collaboration between the Laboratory and the Clinical Follow-Up of the Patients - Svetlana Lajic; Leif Karlsson; Rolf H. Zetterström; Henrik Falhammar; Anna Nordenström (MDPI AG, 2020)
Neonatal screening for congenital adrenal hyperplasia due to 21-hydroxylase deficiency is now performed in an increasing number of countries all over the world. The main goal of the screening is to achieve early diagnosis and treatment in order to prevent neonatal salt-crisis and death. The screening laboratory can also play an important role in increasing the general awareness of the disease and act as the source of information and education for clinicians to facilitate improved initial care, ensure prompt and correct glucocorticoid dosing to optimize the long-term outcome for the patients. A National CAH Registry and CYP21A2 genotyping provide valuable information both for evaluating the screening program and the clinical outcome. The Swedish experience is described.